The Enduring Legacy of Shaykh Khadir Ṣalāhudeen Apaokagi: Shaping Islam in Ilorin Emirates - Azeez, Olamilekan Rasheed; Abdulmalik, Dhikrullah (UAS PRESS, 2024)
This research explores the contributions of Muslim schools to the development of Islam in Ilorin Emirates, specifically Shaykh Khadir Salāhud-Deen Apaokagi. Apaokagi, a prominent scholar in the twentieth century, played a significant role in religious propagation in Ilorin. He began as a student and rose to the rank of Muftī, serving as a teacher, preacher, writer, society founder, and Arabic school founder. His contributions in Ọwọ were particularly significant and inspiring. Apaokagi also served as a mentor to many professors in Islamic studies and Arabic language. The research used historical, analytical, and phenomenological methods to analyze his contributions to the development of Islam in Ilorin and Ọwọ. Shaykh Khadir Salāhuddin Apaokagi was a significant Muslim who contributed significantly to Ilorin and Ọwọ, establishing the Ilorin Iftā institution. Apaokagi's contributions to developing Ansārul Islam society in Nigeria and learning will remain indelible. In conclusion, Shaykh Khadir Ṣalāhudeen Apaokagi's contributions, leadership and social engagement shaped the region's religious, social, and intellectual landscape. His teachings continue to enrich Ilorin's spiritual and social fabric, while his writings serve as a vital resource for future generations. His influence on inclusivity and societal challenges continues to resonate, contributing to peaceful coexistence.